THE RELATIONSHIP OF STRESS WITH THE BEHAVIOR OF CONSUMING CAFFEINATED FOOD AND BEVERAGES IN NURSING STUDENTS AT BANJARMASIN UNIVERSITY - Yuliani Budiyarti (Jurnal Ilmiah Hospitality, 2022)
Academic demands and assignments can be one of the etiologies of stress which has an impact on physical and psychological health so that it causes unfavorable behavior, one of which is towards consuming food and drinks that contain caffeine. This study aims to determine the relationship between stress and the behavior of consuming caffeinated food and drinks in female students at the University of Banjarmasin. This type of research is descriptive analytic with cross sectional design. All populations in this study were used as research samples, namely final year female students and 171 female students undergoing professional nursing education. Test analysis using Spearman rank test. The results showed that the p value was 0.000 <0.05 so that there was a relationship between stress and the behavior of consuming caffeinated food and drinks in female students with. The level of stress experienced by a person is one of the things that contributes to behavior in consuming various types of food and drinks, including those containing caffeine